Western corn rootworm adult activity and immigrant resistance to Bt traits in first-year maize - Lance J. Meinke; Jordan D. Reinders; James Clothier; Jeffrey T. Krumm; Clinton D. Pilcher; Matthew W. Carroll; Graham P. Head (PLoS ONE, 2025)
The western corn rootworm (WCR) Diabrotica virgifera virgifera LeConte is an important insect pest of maize (Zea mays L.) in the midwestern United States of America (USA) and has evolved resistance to maize hybrids producing toxins from the bacterium Bacillus thuringiensis Berliner (Bt). This study was conducted in a landscape with a high proportion of continuous maize (maize planted ≥ two consecutive years) during 2021–2022 in northeast Nebraska, USA to increase our understanding of adult WCR activity in first-year maize and the introduction of Bt resistance by WCR immigrants. Pherocon AM unbaited sticky traps were placed at ear height in first-year maize fields and replaced weekly during adult WCR activity periods to determine density and gender of captured adults. Maize and WCR phenological interactions plus gender-specific behaviors appeared to be key determinants of WCR activity in first-year maize. Comparison of adult emergence and root injury in first- and second-year maize fields confirmed that crop rotation reduces a WCR population to near-zero. Field collections of adults were made from first-year and some adjacent continuous maize fields to estimate Bt susceptibility with Bt bioassays of F1 progeny. Similar resistance levels were observed in WCR collections from first-year and many adjacent continuous maize fields. Aggregate study results suggest adjacent maize fields were a major contributor of WCR immigrants. Significant variation in WCR immigration/ colonization and associated Bt resistance levels were observed in first-year maize, so scouting of first-year maize fields is recommended to match appropriate WCR management approaches to relative risk of injury in second-year maize.